Arginine methylation‐dependent LSD1 stability promotes invasion and metastasis of breast cancer. (12th December 2019) - Liu, Jiwei; Feng, Jingxin; Li, Lili; Lin, Luyao; Ji, Jiafei; Lin, Cong; Liu, Lingxia; Zhang, Na; Duan, Dandan; Li, Zhongwei; Huang, Baiqu; Zhang, Yu; et al.
Abstract: Histone lysine demethylase 1 (LSD1), the first identified histone demethylase, is overexpressed in multiple tumor types, including breast cancer. However, the mechanisms that cause LSD1 dysregulation in breast cancer remain largely unclear. Here, we report that protein arginine methyltransferase 4 (PRMT4 or CARM1) dimethylates LSD1 at R838, which promotes the binding of the deubiquitinase USP7, resulting in the deubiquitination and stabilization of LSD1. Moreover, CARM1‐ and USP7‐dependent LSD1 stabilization plays a key role in repressing E‐cadherin and activating vimentin transcription through promoter H3K4me2 and H3K9me2 demethylation, respectively, which promotes invasion and metastasis of breast cancer cells. Consistently, LSD1 arginine methylation levels correlate with tumor grade in human malignant breast carcinoma samples. Our findings unveil a unique mechanism controlling LSD1 stability by arginine methylation, also highlighting the role of the CARM1‐USP7‐LSD1 axis in breast cancer progression. Synopsis: The protein arginine methyltransferase CARM1 targets the histone lysine demethylase LSD1 and promotes its stabilization via USP7‐dependent deubiqutination. Stabilised LSD1 enhances migration and invasion of breast cancer cells, further facilitating metastasis. Methylation of LSD1 by CARM1 recruits USP7, which results in the deubiquitination and stabilisation of LSD1. LSD1 methylation catalyzed by CARM1 promotes breast cancer cell invasion and metastasis. Methylated LSD1 binds to the E‐cadherin and vimentin genes, leading to their respective repression or activation. LSD1 arginine methylation levels correlate with tumor grade in human breast cancer samples. Abstract : The protein arginine methyltransferase CARM1 targets the histone lysine demethylase LSD1 and promotes its stabilization via USP7‐dependent deubiqutination. Stabilised LSD1 enhances migration and invasion of breast cancer cells, further facilitating metastasis.